2018
DOI: 10.1007/s10935-018-0511-1
|View full text |Cite
|
Sign up to set email alerts
|

Employment and Other Income Sources Among Homeless Youth

Abstract: Homeless youth report high rates of unemployment. While homeless serving agencies usually offer employment services, most homeless youth are disengaged from homeless service agencies, and a limited number of studies have examined employment and other income sources among service disconnected youth. Our study examined income sources and change in income among service disconnected youth, all of whom received Strengths-Based Outreach and Advocacy (SBOA, N = 79). Findings revealed that over time employment and leg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Three studies are reported in representing four papers ( Table 2 ). Slesnick et al [ 16 ] and Wu et al [ 36 ] are geographically located in the US and report outcomes following a randomized controlled trial. Lynn et al [ 37 ] study was also located in the US, and Adams et al [ 38 ] was based in Ireland.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies are reported in representing four papers ( Table 2 ). Slesnick et al [ 16 ] and Wu et al [ 36 ] are geographically located in the US and report outcomes following a randomized controlled trial. Lynn et al [ 37 ] study was also located in the US, and Adams et al [ 38 ] was based in Ireland.…”
Section: Resultsmentioning
confidence: 99%
“…Lynn et al [ 37 ] study was also located in the US, and Adams et al [ 38 ] was based in Ireland. The study populations consist of adult participants and staff members [ 38 ], adolescents and their parents [ 37 ] and young adults aged 18 to 24 years [ 16 , 36 ]. All studies report randomized controlled trial methods, except for Adams et al [ 38 ] reporting a mixed-methods study ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Employment variables include current employment status, number of different paid jobs in the past 3 months, and longest time spent in any one job in the past 3 months [ 91 ]. Economic stability is assessed in terms of income in the past 30 days from various sources (e.g., job, relatives or friends, government assistance, street economy) [ 92 ], and items asking how much of a problem it was in the past 3 months to get clothes, medical care/treatment, a place to clean up, a clean and safe place to sleep, and enough to eat, (0 = none to 4 = a great deal ) [ 93 , 94 ]. Housing stability is assessed with items adapted from Tsemberis et al (2007) [ 95 ], asking how often they had spent the night in various locations in the past 3 months (e.g., their own house, apartment or room; someone else’s apartment or house; emergency shelter; transitional housing program; outdoors, the street, or a park; car or other private vehicle; abandoned building; hotel/motel; 0 = never to 7 = everyday ).…”
Section: Methodsmentioning
confidence: 99%